Dimensional Deviation Management for Selective Laser Melted Ti6Al4V Alloy Blade - Li, Mingpei; Li, Jiuxiao; Yang, Dongye; He, Bo (Frontiers in Materials, 2020)
Selective laser melting (SLM) is prone to generate large thermal stresses, which could induce a heavy geometric change in the parts. In this study, Ti6Al4V blade was prepared by Selective laser melting (SLM). Microstructure, dimensional deviation and residual stress were investigated. Microstructure is acicular α' martensite in prior columnar β grain. The smaller the grain size, the larger the dimensional deviation. The directions of dimensional deviation at the leading and trailing edges of blade are opposite to those in the middle. The distribution of dimensional deviation exhibits a parabolic law at the trailing edge of blade. The thermal stress is big at the edges of the blade body. The large tensile stress along the edges of the blade body caused the edges to deform toward the suction side of the blade. The residual stress distribution of the pressure surface by the XRD measured has a good agreement with thermal stress distribution by calculated.